Lived experiences of nurses who have been assaulted by patients at a psychiatric hospital in the Western Cape. - Yusi, Phikisile Thiery (University of the Western Cape, 2016)
Magister Curationis - MCur === Background: Nurses, because of their close contact with these patients, are frequently victims of assault. The aim of the study is to explore and describe the lived experiences of nurses, who have been assaulted by patients at a Western Cape psychiatric hospital. Research Design: A qualitative approach, using a phenomenological research design was used to achieve the aim of the study. The target population was nurses, who are employed at the hospital under study. A purposive sampling, consisting of six nurses, was selected to participate in this study. Data were collected by means of unstructured interviews with nurses who met the inclusion criteria. Data saturation was reached after the sixth individual interview. The interviews were audio taped and transcribed, verbatim, and field notes were taken, as well. Collaizi’s method of data analysis was used to analyse the data and to identify themes and categories. The major themes that emerged were: Self-care incongruent to intrapersonal interest; Personal responses to trauma; Incongruence between patient behaviour and participant work experience; unprotected staff vulnerable to patient aggression; required and received supportive interventions. Ethical clearance was obtained from the Senate Ethics Committee at the University of the Western Cape. Permission to conduct the study was obtained from the Research Ethics Committee at a psychiatric hospital under study, as well as from the Department of Health, Western Cape. Participants were drawn from different units of the hospital. Findings: The findings revealed that nurses working at this psychiatric hospital frequently encounter assault and violence by patients, while providing care, to the extent that they view the workplace environment as unsafe and insecure. The way they experienced the assaults had some similarities; they all complained that they felt neglected by management after the assaults and that they experienced multiple bodily reactions to trauma. Recommendations: From the data gathered, it appeared that nurses were calling for support from those in authority, be it supervisors or hospital management. Some of the recommendations made by the researcher were: regular refresher courses on self-awareness training; counselling/debriefing; skills development workshops on management of aggression; and the feasibility of paying a special allowance to staff. Conclusion: The study revealed that lack of management support perpetuates the cycle of violence experienced, which, in most incidents, has a spill over effect in the personal lives of the nurses, who have been assaulted by patients. It is the researcher’s belief that nurses should be supported in this stressful environment.